Cohort profile: the ESC EURObservational Research Programme Non-ST-segment elevation myocardial infraction (NSTEMI) Registry - Nadarajah, Ramesh; Ludman, Peter; Appelman, Yolande; Brugaletta, Salvatore; Budaj, Andrzej; Bueno, Hector; Huber, Kurt; Kunadian, Vijay; Leonardi, Sergio; Lettino, Maddalena; Milasinovic, Dejan; Gale, Chris P and the NSTEMI Investigators; et al. (Oxford Academic, 2022)
The European Society of Cardiology (ESC) EURObservational Research Programme (EORP) Non-ST-segment elevation myocardial infarction (NSTEMI) Registry aims to identify international patterns in NSTEMI management in clinical practice and outcomes against the 2015 ESC Guidelines for the management of acute coronary syndromes in patients presenting without ST-segment-elevation.
Keywords: EORP; NSTEMI; Non-interventional; Observational; Prospective; Registry